PENGARUH PROFITABILITAS, LEVERAGE, DAN KUALITAS AUDIT TERHADAP TAX AVOIDANCE - Erwin Sulistiono (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2018)
The objective of the empitical study is to examine and to analyze the effect of Profitability, Leverage, and Audit Quality on Tax Avoidance with Size of the Company as moderating variable. The sample of the empirical study is the mining company that listed in Bursa Efek Indonesia (BEI) in 2012-2016. This research uses multiple regression analysis as hypothesis testing. The result of the empirical study are (1) Profitability had negative significant influence to Tax Avoidance, (2) Leverage had not significant influence to Tax Avoidance, (3) Audit Quality had positive significant influence to Tax Avoidance, (4) Size of The Company had the strengthens positive significant influence between profitability to Tax Avoidance, (5) Size of The Company had the strengthens positive significant influence between leverage to Tax Avoidance, (6) Size of The Company had the weakens negative moderating significant influence between audit quality to Tax Avoidance.